Labour Market Outcomes of Itinerant Workers in Rural India. (14th July 2015) - Agrawal, Tushar; Chandrasekhar, S.
Abstract: This paper examines the characteristics, wages and mobility of short‐term migrants in India using a nationally representative database on migration. We find that an individual is more likely to be a short‐term migrant if he or she is from a district with a higher concentration of workers in the construction industry. Using instrumental variable method, we find that short‐term migrants are likely to earn lower wages compared with non‐short‐term migrants. Finally, we model the transition of short‐term migrant workers from one sector to another, drawing on the literature on income and occupational mobility. Copyright © 2015 John Wiley & Sons, Ltd.